Nickel-Catalyzed Asymmetric Cross-Electrophile Coupling Reactions - Jin, Youxiang; Wang, Chuan (Synlett, 2020)
The merger of cross-electrophile coupling and asymmetric catalysis provides a novel approach to the preparation of optically active compounds. This method is often endowed with high step economy, mild conditions, and excellent tolerance of functional groups. Recent advances in the research field of nickel-catalyzed asymmetric cross-electrophile coupling reactions are highlighted in this concise Synpacts article.1 Introduction2 Asymmetric Cross-Electrophile Coupling Reactions between Organohalides3 Asymmetric Electrophilic Ring-Opening Reactions4 Asymmetric Electrophilic Difunctionalization of Alkenes4.1 Two-Component Electrophilic Difunctionalization of Alkenes Involving Arylnickelation as an Enantiodetermining Step4.2 Two-Component Electrophilic Difunctionalization of Alkenes Involving Carbamoylnickelation as an Enantiodetermining Step4.3 Three-Component Electrophilic Difunctionalization of Alkenes5 Asymmetric Electrophilic Functionalization of Carbonyl Compounds6 Summary
Keywords: nickel catalysis; asymmetric catalysis; reductive cross-coupling; umpolung; electrophiles